2010
DOI: 10.4038/tar.v21i1.2582
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Pre-cooling, Application of Natural Extracts and Packaging on the Storage Quality of Apple (<i>Malus domestica</i>) cv. Royal Delicious

Abstract: During recent years, global concern for protection of the environment has led researchers to investigate the use of natural flora as one of the sources for crop protection. The present investigation was also directed to find out the natural and ecofriendly fruit coating, package and storage alternatives for the extension of the storage life of apple (Malus domestica) cv. 'Royal Delicious'. Surface coating of apple with 1, 1.5, 2% neem oil (Azadirachta indica) and 10, 15, 20% extracts of marigold flower (Tagete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Perusal of data presented in Table 1 revealed that skin coating with 1% neem oil provided complete control of all the fungal decays under study. Similar observations were recorded by Wijewardane and Guleria (2009). Steinhauer (1987) isolated a compound with antifungal activity from neem kernal extracts which has been used for the control of phytopathogenic fungi such as Penicillium expansum.…”
Section: Resultssupporting
confidence: 73%
“…Perusal of data presented in Table 1 revealed that skin coating with 1% neem oil provided complete control of all the fungal decays under study. Similar observations were recorded by Wijewardane and Guleria (2009). Steinhauer (1987) isolated a compound with antifungal activity from neem kernal extracts which has been used for the control of phytopathogenic fungi such as Penicillium expansum.…”
Section: Resultssupporting
confidence: 73%
“…Mahajan et al (2013) detected least PLW (3.5 %) in shrink packed pear fruits as compared to unpacked control fruits (6.20 %). Maximum moisture retention (87.4 %) reported in plastic bag wrapped guava stored at 16°C in shrink wrapped Royal-delicious apples and in Nagpur Mandarin (Miano and Jokhio 2010;Wijewardane and Guleria 2009) may be due to retardation in respiration, evapo-transpiration and metabolic processes. The impact of LDPE film used in present study was comparative to HDPE film in PLW reduction of packed grape fruits, Shamouti orange and lemons (Jawandha et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Shrink film maintained superior quality of pear fruits by significant reductions in weight loss, total soluble solids, desired firmness and extended storage life up to 3 weeks in contrast to LDPE and HDPE films (Mahajan et al 2013). Packaging of apples with CFB boxes, polyethylene liners and shrink wrapped tray in storage conditions (2±1°C, 85-90 % RH) have desired effect on physico-chemical characteristics and retained better storage life (Wijewardane and Guleria 2009).…”
Section: Introductionmentioning
confidence: 98%
“…The satisfactory control of the fungal diseases by using various chemicals has been documented in the literature (Choulwar et al, 1988, Maheshwari at al, .1991, Abdul et al, 1995. However, global concern for protection of the environment has led researchers to investigate the use of natural flora as one of the sources for crop protection (Wijewardane et al,. 2009).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%